The Influence of News Construction and Netizen Response to the Hoax News in Online Media - Adhiarso, Dendy Suseno; Utari, Prahastiwi; Hastjarjo, Sri (Jurnal The Messenger, 2018)
This study aims to determine the effect of news in online media on the thoughts and behavior of a person, because the impact is very strong in shaping public opinion. This study uses theory of mass communication, news construction, netizen response, online media. The research method used quantitative descriptive analysis with online data collection techniques. Conclusion of research (1) News construction have positive effect to reporting hoax in online media, meaning that news construction which is loaded and created by online media will influence hoax news dissemination. (2) The netizen response positively affects the news of hoaxes in the online media, meaning more and more netizens respond to hoax news, hoax news will be wider. (3) News construction and netizen responses have a positive and significant influence on hoax news in media online, meaning that these two variables give a significant influence in the preaching of hoax in online media.